The Impact of Credit Risk, Capital Adequacy, Liquidity, and Efficiency on Return on Assets in Indonesian Banking - Sparta; Aura Nanda Safhira (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2026)
This study aims to determine the effect of credit risk, capital adequacy, liquidity and efficiency on return on assets of banks in Indonesia with the control variable bank size. This research was conducted at Conventional Commercial Banks listed on the Indonesia Stock Exchange for the period 2019 to 2023. The research population is the annual report of conventional banks in Indonesia so that the number of samples obtained is 37 banks using purposive sampling method. The analysis method used is data panel analysis. The results showed that credit risk has no effect on return on assets, capital adequacy has no effect on return on assets, liquidity has a significant positive effect on return on assets, efficiency has a significant positive effect on return on assets and bank size has an effect on return on assets. The managerial implications of this study indicate that despite increased credit risk, banks in Indonesia can still maintain profitability through strengthening risk management, optimizing capital utilization, balanced liquidity management, improving operational efficiency, and strategically managing bank size growth. The novelty of this research lies in its use of the most recent period covering the pandemic and recovery phase, as well as the integration of key banking indicators into a comprehensive empirical model. Managerial implications highlight the need for strengthening liquidity management, enhancing operational efficiency, and optimizing bank scale to maintain profitability in a dynamic economic environment.